Research on digital twin network capability maturity model of telecom operators - Shanshan LI; Jianhong XU; Tao LI; Yongjian ZHAO; Zhifei LIU (Dianxin kexue)
The digital twin network is an important direction for the transformation and upgrading of the communication industry, and a key lever for telecom operators to implement national strategies and empower the digital economy.The research results of digital twin maturity in the industry were drawn on, the connotation of digital twin network was analyzed, and a set of digital twin network capability maturity model and evaluation method suitable for telecom operators was put forward.Through systematic description of the development stage of digital twin networks and quantitative evaluation of the maturity of digital twin networks capability, it is helpful for operators to identify technical or organizational weaknesses, improve expected results, and promote innovation and collaboration among different organizations in the industry.